Técnicas de desarrollo de las macro destrezas lingüísticas del área de lengua y literatura de los estudiantes del octavo, noveno y décimo año de educación general básica, del centro educativo ciudad de Ventanas, del cantón Ventanas, provincia los Ríos, periodo lectivo 2011-2012. - Roca Calderón, Luisana Verónica (2012)
The present investigation allows us to know the forms of communicating ideas, information and the humanity's messages have varied through the time. The macro dexterities in the area of Language and Literature are talkative abilities developed in the human being so that this can interaction in their social environment, they can being of understanding and of expression: Dexterities of understanding are to know how to listen, to know how to read and the expression dexterities are, to know how to speak, to know how to write. The present investigation is justified since it is of supreme importance that the teachers worry to develop the macro dexterities of their students because of it depends it in great way the academic yield. In the initial part all the aspects related to the topic are detailed, the antecedents of the investigation unit, the problem to be, the justification of the investigation, the objectives that are sought to reach, as well as the work hypothesis and their respective Operacionalización. In the Capítulo I the Theoretical Marco is described that contains the scientific theory, the mark referencial, legal mark and conceptual theory, the same ones that it contains the sustenance of the whole investigation, under which is based of the study. In the Chapter II the methodological strategies are detailed, in which the methods are described, technical and instruments to achieve the gathering of the data in the field investigation, in other words the operative aspects of the same one. In the chapter III we analyze and we interpret the results of the bars that the students went more than they like the questionnaire because they can investigate this way to obtain better results. Lastly in the Chapter IV he/she is The proposal it is to solve the problem like to provide to the educational ones a methodological guide with technical and instruments that it facilitates the process of evaluation of the macrodestreza in the area of Language and Literature